Online Learning for Dummies illustrations - Manning, Susan; Johnson, Kevin E. 1972-; Vandervelde, Joan (Hoboken, NJ John Wiley & Sons, Inc., 2021)
"Whether you're a college student, adult learner, or professional in continuing education, some--and sometimes all--of your learning will happen in a virtual classroom. This book is your friendly guide to the fast-growing possibilities of this world, from choosing the right course and mastering the software to polishing up your online communication and study skills. Whatever you want from your study experience--school success, professional development, or just pursuing your passion--this is your road map to online educational success!"--Page 4 of cover.
Introduction -- Part 1: Introducing a different kind of learning. Planning for your online learning journey ; The traits and benefits of online learning ; The equipment and skills you need to succeed -- Part 2: Preparing to be a learner. Discovering what's available online ; Doing your homework: evaluating schools ; Applying to school and securing the cash ; Getting accepted and prepping for class ; Mentally preparing and having a technology mindset -- Part 3: The virtual classroom. Navigating the learning environment ; Meeting the people in (and around) your classroom ; Communicating clearly online ; Developing good study habits for online courses ; Getting a handle on group dynamics ; Recognizing we are global ; Understanding netiquette and ethical behavior ; Finishing and submitting your assignments ; Building a portfolio of work -- Part 4: Special considerations in online learning. Educating students from kindergarten through high school ; Accessibility in online education -- Part 5: The part of tens. Ten myths about online learning ; Ten best practices for online learners--including self-care.
Includes index.
"Learning made easy"--Cover.
"Identify the best online program for you. Get organized to succeed at learning at a distance. Be the best learner you can be"--Cover
Keywords: Education -- Computer network resources; Education -- Effect of technological innovations on; Educational technology; Internet in education